Homonymous Hemianopia Secondary to A Long Fusiform Aneurysm of Posterior Cerebral Artery in A Patient with Connective Tissue Disease - Pinto Desti Ramadhoni; Asep Riswandi (AKSONA, 2022)
Highlight: Fusiform aneurysms are uncommon, accounting for only 1% of total intracranial aneurysms, and posterior circulation involvement is only 3-13% of cases of intracranial aneurysms. Connective tissue diseases are very rare as the cause of this vasculopathy. Homonymous hemianopia due to the mass effect or dilated blood vessels compressing the left optic tract.   ABSTRACT Introduction: Fusiform aneurysms are uncommon, accounting for 1% of all intracranial aneurysms. Dissection and atherosclerosis are the main causes of this vasculopathy, but connective tissue disease is a very uncommon cause. Ehlers-Danlos Syndrome is the most common connective tissue disease, accounting for  11% of all cases. Symptoms depend on the location and size of the aneurysm, including headaches, blurred or double vision, and focal neurological deficits. Case: A 36-year-old man suddenly experienced blurred vision in both eyes on the right, starting with a chronic left-sided headache and no history of cardiovascular disease. In the confrontation test, Humphrey gave the right homonymous hemianopia. A head CT scan showed a lobulated lesion which showed enhancement in the left suprasellar region, and cerebral digital subtraction angiography (DSA) gave the impression of a long fusiform aneurysm L PCA. Clinically, the patient’s skin on the left side of his face was darker than on the right, his skin was more elastic, and his blood vessels were wider and more prominent on the side of the fusiform aneurysm. Conclusion: Posterior circulation involvement is only 3-13% of cases of intracranial aneurysms. Many cases of intracranial aneurysms are not detected before rupture, resulting in delays in treatment. Surgical or endovascular surgery can be performed if the size is >10 mm and causes clinical symptoms. Symptoms of ischemia are managed with antiplatelets or anticoagulants. Incidentally detected unruptured aneurysms are generally managed conservatively because of the highly friable nature of the blood vessels in patients with connective tissue diseases.